Implementasi Asesmen Peta Konsep Untuk Mengukur Struktur Kognitif Dan Berpikir Kritis Dalam Pembelajaran Berbasis Masalah - Jeje Sudarja; Sofyan Hasanudin Nur; Abdul Muis (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2018)
Learning assessment which is usually used has not facilitated the developing of cognitive structure and critical thinking in problem solving. It gives an effect to the learning result which is not satisfied yet. One of the assessment which develops the meaningful learning is map concept. The aim of the research is to analysis accomplished learning, map concept quality which is arranged by the students, the developing of cognitive structure and critical thinking, the relationship between map concept quality which is arranged by the students and the developing of cognitive structure and critical thinking. The research is a quasi experiment with Randomized Pretest Post Test Control Group Design. The research population is all the 9th grader students in SMPN 1 Karangkancana Kuningan in academic year 2015/2016. The number of the students is 116. The sample of the research is taken by Simple Random Technique, 58 students. The achievement of research result is (1) The accomplished of learning is categorized “good”, every stage of learning in accordance with the planning but still found obstacles. (2) The map quality concept which is categorized “fair” and “bad”, and no category of “high “ , which is designed learning has not been able to facilitate students in the achievement of the four components of the concept maps perfectly. (3) There is a significant progress in structure cognitive and students critical thinking is categorized “fair”, students are not familiar with the of learning that develops the cognitive structure and critical thinking. (4) There is a positive correlation between map concept quality and students critical thinking which is categorized “strong”, and there is linearity unidirectional nature, every increase in the quality of concept maps followed by an increase in critical thinking. (5) The student positive is categorized “almost all”, students are very enthusiastic and very active in learning activities. It can be concluded that map concept assessment can develop cognitive structure and students critical thinking, also, there is a significant relationship between map quality concept and students critical thinkingKeywords : Concept Map Assessment; Cognitive Structure; Critical Thinking;Problem Based Learning